Health-related quality of life and Chlamydia trachomatis infection in sexually experienced female inner-city students: a community-based cross-sectional study. (March 2017) - Sri, Trisha; Southgate, Eleanor; Kerry, Sarah R; Nightingale, Claire; Oakeshott, Pippa
This cross-sectional study was undertaken to compare health-related quality of life (EQ-5D) in women with and without undiagnosed Chlamydia trachomatis infection. We analysed data from 2401 multi-ethnic sexually active female students aged 16–27 years who were recruited to a randomised controlled trial of chlamydia screening – the prevention of pelvic infection trial in 2004–2006. At recruitment, all participants were asked to provide self-taken vaginal swabs for chlamydia testing and to complete a sexual health questionnaire including quality of life (EQ-5D). Most women (69%) had an EQ-5D of one representing 'perfect health' in the five dimensions: mobility, self-care, usual activities, pain/discomfort and anxiety/depression. We therefore compared the proportion of women with an EQ-5D score < 1 implying 'less than perfect health' in women with and without chlamydia infection, and women with symptomatic chlamydia versus the remainder. The proportion of women with EQ-5D score < 1 was similar in women with and without undiagnosed chlamydia: 34% (47/138) versus 31% (697/2263; RR 1.11, 95% CI 0.87 to 1.41). However, more women with symptomatic chlamydia had EQ-5D score < 1 than the remainder: 45% (25/55) versus 31% (714/2319; RR 1.47, CI 1.10 to 1.98). In this community-based study, EQ-5D scores were similar in women with and without undiagnosed chlamydia. However, a higher proportion of women with symptomatic chlamydia infection had 'less than perfect health'. Undiagnosed chlamydia infection may not have a major short-term effect on health-related quality of life, but EQ-5D may not be the best tool to measure it in this group.